THE EFFECTIVENESS OF THE STORY-TELLING METHOD WITH STORY APRONS ON INDONESIAN SPEAKING SKILLS IN EARLY CHILDHOOD - Warmansyah, Jhoni; Fitri, Winda Syah; Permatasari, Dola; Rahmi, Dian Aulia (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
This study aims to determine the effectiveness of a Story Telling Method using story aprons on the ability to speak Indonesian in early childhood. Quasi-experimental research to determine the effect of treatment. Sampling using a random sampling technique. The research instrument was a test of Indonesian speaking ability in children which was developed through theoretical studies from several experts, then continued with normality tests, homogeneity tests, and hypothesis testing using the t-test. The results obtained were that the t-value was greater than t -Table thus the Story Telling method with the media of story aprons is effective in improving the ability to speak Indonesian in early childhood. The ability to speak Indonesian well from an early age will affect the child's development in the future.